KOMUNIKASI GURU DAN SISWA DI SEKOLAH MENENGAH ATAS DALAM PENCEGAHAN PERUNDUNGAN DI KOTA BOGOR - Aminah, Ratih Siti; Pramono, Firdanianty; Salsabila, Audya Shafa (Media Bahasa, Sastra, dan Budaya Wahana, 2025)
This study examines the relationship between teacher and student communication in preventing bullying behavior in high schools in Bogor City, which is a buffer zone for the nation's capital, a tourist destination, and a residential area for residents of Greater Jakarta (Jabodetabek). This survey research used a quantitative approach, with 195 students in grade XI, who were randomly selected as respondents. Data collection was carried out using a questionnaire filled out directly by the students, under supervision. The statements in the questionnaire included elements of openness of communication and indicators of socialization. School selection was carried out randomly, if each school has an equal opportunity for Perundungan behavior to occur. Data processing was carried out using SPSS 24. The results showed that elements of teacher and student communication including openness, empathy, supportive attitudes, positive attitudes, and equality have a very strong relationship with bullying prevention, with a correlation value of 0.804. Two-way communication between teachers and students, the existence of mutual respect, and the appropriate way of conveying messages contribute to creating a safe and comfortable school environment. This situation is intertwined with students' willingness to report bullying to teachers when they notice it, and their active involvement in prevention efforts. Furthermore, the measured indicators of physical, verbal, and psikologis bullying indicate the need for stricter supervision and a more inclusive approach to handling bullying.